Pretest of images for the beauty dimension - Mello, Joana José de (2016)
In this work, we present norms concerning the perceived association of two sets of image stimuli with the concept of “beauty”: 40 objects (Study 1) and 40 photos of human faces (Study 2). Participants were presented with a set of words associated with the construct of “beauty” and were subsequently asked to judge each image on how much they considered them to be related with this construct on a 7-point scale (1 – Not at all related; 7 – Very related). The interpretation of means’ confidence intervals distinguish between 40 images, evaluated as “ugly” – with low scores on the beauty dimension – (20 objects and 20 faces), and 28 images evaluated as “beautiful” – with high scores on the beauty dimension – (12 objects and 16 faces). Results are summarized and photos made available to support future research requiring beauty and/or ugly stimulus.